Biochar-based materials for oil industry wastewater treatment: a review - Díaz García, Bryan Manuel (2023)
Water contamination has become a serious issue that affects the world and all living beings. Domestic and industrial wastewaters contain high amounts of chemicals that affect the ecosystem and human health. Among the pollutants present in industrial and domestic wastewaters are urea, heavy metals, coliforms, bacteria, fats, etc., which are highly toxic for the environment. This is the case of wastewaters from oil industries, which are generated from the crude oil extraction and contain undesired and toxic compounds (e.g., heavy metals and refractory substances. These wastewaters can also contain very harmful compounds such as dissolved salts and gases (e.g., cations, anions, H2S, CO). Multiple alternatives for the treatment of these wastewaters have been developed at different scales, such as primary and tertiary treatments (e.g., adsorption). Sedimentation, chemical coagulation, flotation and filtration have been the most common wastewater treatment processes. On the other hand, recent works have reported novel alternatives to treat wastewaters containing toxic and high pollutant load. Among them, the use of BC has become a suitable alternative for environmental remediation. Biochar is a carbonaceous material with interesting physicochemical properties (e.g. high surface area and porosity) and can be prepared by different synthesis methods, using agricultural wastes, like branches of banana rachis, cocoa shells, cane bagasse, etc. This work is a review thesis that is based on a general description of BC for environmental remediation focused on the remediation of wastewater from the oil industry. In addition, the production, synthesis and multiple uses of BC have been analyzed. This material has shown a high capacity for the adsorption of toxic compounds from oil industry wastewaters. Therefore, this work focuses on the study of BC from agricultural wastes for the treatment of oil industry wastewaters, which contributes to the circular economy and the environmental remediation through the mitigation of the effects generated by the pollutant and toxic load generated by this industry.